A Classification of Feminist Theories - Wendling, Karen (Les ateliers de l'éthique / The Ethics Forum, 2008)
In this paper I criticize Alison Jaggar’s descriptions of feminist political theories. I propose an alternative classification of feminist theories that I think more accurately reflects the multiplication of feminist theories and philosophies. There are two main categories, “street theory” and academic theories, each with two sub-divisions, political spectrum and “differences” under street theory, and directly and indirectly political analyses under academic theories. My view explains why there are no radical feminists outside of North America and why there are so few socialist feminists inside North America. I argue, controversially, that radical feminism is a radical version of liberalism. I argue that “difference” feminist theories – theory by and about feminists of colour, queer feminists, feminists with disabilities and so on – belong in a separate sub-category of street theory, because they’ve had profound effects on feminist activism not tracked by traditional left-to-right classifications. Finally, I argue that, while academic feminist theories such as feminist existentialism or feminist sociological theory are generally unconnected to movement activism, they provide important feminist insights that may become important to activists later. I conclude by showing the advantages of my classification over Jaggar’s views.